(untitled) (Research, Society and Development, 2022)
The degree in Biological Sciences is challenging and at the same time enriching: it allows the understanding that science teaching has contents that can – and shall – be approached in several ways, making use of methodological resources seeking an egalitarian learning. Under this perspective, this essay had the aim of developing a courseware for inclusive teaching of sciences focused on ecology to people with intellectual disabilities (ID). Based on a theoretical framework on the topic, which suggests how the didactics to people with ID should be, an Ecological Track was developed in the classroom of a 7th grade class of elementary school in a public institution of Santa Rosa/RS, in which there was a student that was diagnosed with this disability. The activity had a great participation of the students and achieved the expected results, which were: to develop an inclusive activity that guided the students to reflect upon how much the human being intervene in the environment and what are the possible changes in behavior we can adopt to minimize these impacts. Throughout a questionnaire, this study also allowed to understand how the inclusive teaching is understood by some teachers.